Psychological support for telework in labor organizations - Solf Zárate, Arturo (2023)
Currently, as a consequence of the covid-19 pandemic, it has become relevant to carry out work from a different environment than the local organization, using information and communication technologies (ICT) as the main resource, a work modality known as Telework. This document is aimed at disseminating the main contributions that psychologists can make in favor of the performance and well-being of the personnel involved. Previously, a theoretical framework based on an investigation of the respective bibliography is presented.